Harbour porpoises (Phocoena phocoena) and minke whales (Balaenoptera acutorostrata) observed during land-based surveys in The Minch, north-west Scotland. (September 2014) - Dolman, Sarah J.; Hodgins, Nicola K.; MacLeod, Colin D.; Pierce, Graham J.; Weir, Caroline R.
<x content-type="archive" xml:space="preserve">Abstract</x> The waters off north-west Scotland are known to provide important habitat for the harbour porpoise (Phocoena phocoena) and the minke whale (Balaenoptera acutorostrata). Between October 2008 and April 2011, systematic land-based surveys were carried out to assess the seasonal occurrence, group size and group behaviours of both species in a study area located off Melvaig, near Gairloch. Data were collected on 47 separate days, with a total of 4543 minutes of survey effort (in sea states ≤3) recorded during the spring months and 8204 minutes of effort during the autumn. A total of 189 sightings of marine fauna were recorded, comprising 126 cetacean sightings, 50 seal sightings and 13 sightings of basking sharks (Cetorhinus maximus). Six species of cetacean were identified, with most sightings comprising harbour porpoise (N = 72) or minke whale (N = 38). Harbour porpoise abundance was higher in autumn than in spring and there was a variation between years in numbers of minke whales sighted. In porpoises, sea state and cloud cover both influenced sightings and increasing sea state influenced survey area. Foraging behaviour was exhibited in 13% of harbour porpoise sightings and 34% of minke whale sightings. Results demonstrate a regular occurrence of harbour porpoises and minke whales in nearshore waters off Gairloch. Densities are comparable to boat surveys in the region and so support the use of land-based watches as a potential longer-term monitoring method for these species in coastal waters. Given the regular use of this area by these two European Protected Species, as well as the occurrence of a range of human activities potentially affecting them in the region, it may be appropriate to consider protecting this area for their conservation.